2022
DOI: 10.3389/fphys.2022.854606
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis Is Associated With Heart Failure: A Population-Based Study (NHANES III)

Abstract: Objectives: The aim of this study was to investigate the relationship between periodontitis and heart failure using the Third National Health and Nutrition Examination Survey (NHANES III).Methods: Participants who had received a periodontal examination were included and investigated for the occurrence of heart failure. The included participants were divided into no/mild periodontitis and moderate/severe periodontitis groups according to their periodontal status. Weighted prevalence of heart failure was calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…Participants with a higher PIR, higher education levels and who were non‐smokers had a lower prevalence of periodontitis. These findings are consistent with previous studies on periodontitis using NHANES database (Gay et al, 2018; Li et al, 2022; Montero et al, 2019; Yan et al, 2022), highlighting the importance of controlling for covariates when evaluating the relationship between probiotic intake and periodontitis. Additionally, our results indicate that participants without hyperlipidaemia, hypertension or diabetes had significantly lower prevalence of periodontitis, suggesting an association between these conditions and periodontitis.…”
Section: Discussionsupporting
confidence: 92%
“…Participants with a higher PIR, higher education levels and who were non‐smokers had a lower prevalence of periodontitis. These findings are consistent with previous studies on periodontitis using NHANES database (Gay et al, 2018; Li et al, 2022; Montero et al, 2019; Yan et al, 2022), highlighting the importance of controlling for covariates when evaluating the relationship between probiotic intake and periodontitis. Additionally, our results indicate that participants without hyperlipidaemia, hypertension or diabetes had significantly lower prevalence of periodontitis, suggesting an association between these conditions and periodontitis.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the fact that periodontitis is a common risk factor for heart failure, it is crucial to construct specialized treatment protocols and evaluate the significance of diagnostic accuracy in patients with periodontitis in order to lower the probability of developing heart failure. [41–46] Our research demonstrates that myocardial infarction is a risk factor for heart failure in people with periodontitis. Heart failure is a manifestation of end-stage cardiovascular disease, including myocardial infarction.…”
Section: Discussionmentioning
confidence: 87%
“…MAPSE lat values in the PG were also well below the age-related reference values [ 96 ]. Yan et al [ 97 ] showed that the incidence of heart failure in patients with moderate/severe periodontitis was markedly higher compared to no or mild periodontitis. Walther et al [ 98 ] reported an association between severe periodontitis and mid-range-reduced EF, but not with HF in general or echocardiographic variables.…”
Section: Discussionmentioning
confidence: 99%